Penatalaksanaan Fisioterapi Pada Pasien Dengan Systemic Lupus Erithematosus Di Rsud Dr. Moewardi Surakarta - Saputri, Faudea Hayu; , Totok Budi Santoso , S.Fis , MPH (2017)
Background: Systemic Lupus Erithemathosus (SLE) is an immune disease that causes chronic inflammation in the human body causing pain, excessive fatigue, and decreased kinetic quality. In this case, because of the wrong autoantibody activity in detecting antigens so that attacking cells, tissues, and organs will cause physiotherapy problems that is pain and decrease of kinetic quality and possibly other symptoms that can arise such as tighness and spasm. In this case physiotherapy can use the modalities of IRR (Infra Red Radiation), ES (Electrical Stimulation) Interverensial currents, and Exercise. Objective: To know the benefits of physiotherapy management with IRR (Infra Red Radiation) modality, ES (Electrical Stimulation) Interverensial currents, and Exercise. In Sysstemic Lupus Erithematosus (SLE) cases of pain relief, kinetic quality, and functional activity of the patient. Results: After 4 weeks of therapy, the results obtained were decreased pain, increased scope of joint motion, and increased ability of functional activity. Conclusions: IRR (Infra Red Radiation), ES (Electrical Stimulation) Interverensial currents, and Exercise can reduce pain, maintain kinetic quality, and improve the functional ability of the patient